2018
DOI: 10.1111/jdi.12889
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in glucose fluctuations in elderly patients with type 2 diabetes using repaglinide: A randomized controlled trial of repaglinide vs sulfonylurea

Abstract: Switching from SU to Repa improved GA and GA/HbA1c, and had favorable effects on glucose fluctuation in elderly patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Repaglinide is the most effective agent of this class, with a moderate effect on weight gain. Use of repaglinide may be indicated for elderly patients with type 2 diabetes because of the low risk of hypoglycemia, high efficacy on postprandial hyperglycemia, and safe use in renal impairment (65).…”
Section: Diabetes Treatmentsmentioning
confidence: 99%
“…Repaglinide is the most effective agent of this class, with a moderate effect on weight gain. Use of repaglinide may be indicated for elderly patients with type 2 diabetes because of the low risk of hypoglycemia, high efficacy on postprandial hyperglycemia, and safe use in renal impairment (65).…”
Section: Diabetes Treatmentsmentioning
confidence: 99%
“…Repaglinide is another medication which can improve GV by promoting insulin release from the pancreas with a low risk of developing hypoglycemia (Hasslacher, 2003;Jovanovic et al, 2000). It has been reported that elderly patients with T2DM had attenuated glucose fluctuation after switching from sulfonylurea to repaglinide (Lin et al, 2011;Omori et al, 2018). In the present study, we found that acarbose add-on more remarkably reduced GV than repaglinide add-on although both of them may improve GV.…”
Section: Discussionmentioning
confidence: 41%
“…Repaglinide is a hypoglycemic drug that promotes insulin secretion and has the characteristics of quick start, short duration, and rapid metabolism. It has a low risk of hypoglycemia and great effect on postprandial hyperglycemia ( Derosa et al, 2009 ; Fang et al, 2014 ; Moses et al, 1999 ; Omori et al, 2018 ). Combined use of acarbose or repaglinide with metformin or other medications will be needed if glycemic goals are not met.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hypoglycemia risk of glinides is reportedly significantly lower than that of SU . Several studies reported that repaglinide produces less hypoglycemia than SU . Although considering the small number of patients using glinides in the present study, it would seem that at least for older individuals, glinides are more appropriately indicated compared with SU.…”
Section: Discussionmentioning
confidence: 99%